IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK DI KELAS IVB SDN 64/I MUARA BULIAN - Lusi Dwi Yanti; Irfan; M. Zaid; Destrinelli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the mathematics learning process, students tend to be passive because they are less involved in the learning process. The ultimate goal of learning mathematics in elementary school is for students to be skilled in using various mathematical concepts in everyday life. The research method used in this research is Classroom Action Research (CAR), which is also called Classroom Action Research (CAR). The results of this research include grades in the pre-cycle, it is known that of the 26 students there were only 6 students who met the score > KKM (70) while 20 of them had the score < KKM (70). Based on the scores in cycle 1 of the fraction material, it is known that of the 26 students there were only 16 students who met the score > KKM (70) while 10 of them had the score < KKM (70). If examined carefully, this score of 70 is only obtained by a small number of students in the class. So if it is a percentage, it is very far below the specified percentage of total student completion. For this reason, it is very necessary to improve the deficiencies in cycle I learning through the implementation of cycle II actions. Based on the scores in cycle 2 of the block and cube material, it is known that of the 26 students there were only 22 students who met the score > KKM (70) while 4 of them had the score < KKM (70).